2017
DOI: 10.1080/08941939.2017.1296513
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Alpha-Lipoic Acid on Methotrexate-Induced Oxidative Lung Injury in Rats

Abstract: Oxidative damage of MTX in rat lung is partially reduced when combined with ALA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…This suggesting that peroxidative damage to tissues probably commenced after 2 weeks of MTX administration Coleshowers et al [45] . These findings were also similar to other study that stated that the tissue GSH levels in the MTX group were lower than those in the control group [46] . MTX-induced toxicity activates an inflammatory response and significantly increases the production of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…This suggesting that peroxidative damage to tissues probably commenced after 2 weeks of MTX administration Coleshowers et al [45] . These findings were also similar to other study that stated that the tissue GSH levels in the MTX group were lower than those in the control group [46] . MTX-induced toxicity activates an inflammatory response and significantly increases the production of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, oxidative stress is one of the main causes of lung injury induced by MTX. Long-term administration of MTX can induce severe interstitial pneumonia [32] and lung injury [33]. In the other way, it was reported that MTX could also cause severe gastrointestinal reaction.…”
Section: Discussionmentioning
confidence: 99%
“…This drug is used at low doses for the treatment of various inflammatory and autoimmune diseases, including rheumatoid arthritis, juvenile idiopathic arthritis and psoriasis, as well as at high doses for treating various types of cancers [2,3]. However, the efficiency of this agent at high doses or long-term therapy is related to its hepatotoxicity and some of the known side effects include hematologic complications, lung and intestinal toxicity [3,4]. The mechanism of liver damage caused by methotrexate has not been clearly specified; nevertheless, it has been reported that methotrexate causes oxidative stress and inflammation in the liver tissue.…”
Section: Introductionmentioning
confidence: 99%